Comprehensive consultation model for explosion risk in mine atmosphere-CCMER. (December 2019) - Cheng, Jianwei; Mei, Jing; Peng, Siyi; Qi, Chang; Shi, Yu
Highlights: A total of 7 methods to determine the mine gas explosibility is summarized. The explosion risk assessment/trend analysis mathematical models are stated. A PC-based computer package CCMER has been developed. Three basic module programs (Determination, Risk assessment and Trend analysis) are included in this computer package. Abstract: Mine gas explosion is one of the most feared hazards in the coal industry worldwide. More often one gas explosion related accident can cause the death of multiple coal miners. Examination of recent mine explosion disasters that have occurred in the worldwide reveals that most explosions originated from or around the sealed areas. Therefore, a good understanding of the atmospheric status in a sealed coal mine area is crucial in preventing and reducing accidents associated with mine combustible gases and also for planning and implementing a mine rescue strategy. In this paper, a PC based computer gas explosion consultation software model developed by the authors is introduced. This model is called CCMER (Comprehensive Consultation Model for Explosion Risk in Mine Atmosphere). The computer model is a comprehensive, reliable and user-friendly one. The nature of "comprehensive" means the model can be used to consult the explosibility of a gas sample taken from underground atmosphere, can assist engineers to know how explosion dangerous the situation is or what the risk degree is for a not-explosive atmosphere, and also can perform quantified analyses on the changing time span between not-explosive state and explosive state to guide the recuse works. All of those works are very important to mine operators understanding the mine atmosphere and then taking proper measures to control the potential risk. In addition to that, usages of developed computer program are also very easy. Users can operate the program without possessing an in-depth knowledge on computer and mathematical theory. Until today, CCMER has been successfully employed in numerous cases of designing and assessing various mine atmospheres during the past decades. The reliability of mathematical models used in CCMER has also been proven by such applications.